KETERKAITAN MODAL SOSIAL DENGAN STRATEGI KELANGSUNGAN USAHA PEDAGANG SEKTOR INFORMAL DI KAWASAN WADUK MULUR: STUDI KASUS PADA PEDAGANG SEKTOR INFORMAL DI KAWASAN WADUK MULUR KELURAHAN MULUR KECAMATAN BENDOSARI KABUPATEN SUKOHARJO - Suka Mahendra (Jurnal Analisa Sosiologi, 2015)
In this paper, the author explain about “The Relationship Between SocialCapital Merchant Sector Strategy Going Concern Informal in the ReservoirCreep (Case Studies On Social Capital Linkage Business Continuity StrategyAgainst Informal Sector Traders in the Area Mulur Reservoir Mulur VillageDistrict Bendosari Sukoharjo)”, this aims of this research are to know :1)social capital informal sector traders Mulur Reservoir region, 2)businesscontinuity strategy informal sector traders elongation Reservoir region, and3)the influence of social capital relationships with business continuitystrategies in the informal sector traders Mulur Reservoir region. The result ofthis research showed that informal sector traders Mulur Reservoir region havesocial capital that is built in association network RT / RW, study groups,Market Traders Association, and the life cycle (help-help), there is arelationship based on mutual trust (trust), the network is then wokecollaborations, help each other, and obtained many mutual benefit, in whichthere is sustained by norms of formality, respect, honor, mutual. And willalways be colored by the values of obedience, honesty, achievement,individualistic and help. Social capital linkages with business continuity lies inthe elements which are built into the social capital and cooperation wereforged informal sector traders in business continuity activities, where theelements of the business continuity coloring. With the continuity of capital,human resources, production and marketing of social relationships tend to becolored by their participation in the activities of the network, in exchangeactivities goodness (reciprocity) in the life cycle, which has mutual norm inevery social relationship.Keywords : Sosial Capital, Business Continuity, Informal Sector Traders